Morphological and optical characterization of spin-coated CuO nanostructured thin films doped with V, Na, Ba, and Er for enhanced CO2 sensing - Nihed Allouche; Bouzid Boudjema; Radouane Daira; Adel M. El Sayed; Khaled Abdelkarem; Inas A. Ahmed; Mohamed Shaban (Journal of Materials Research and Technology)
Carbon dioxide sensors are crucial for industrial processes and monitoring indoor air quality, but developing low-cost, high-performance sensors that operate at room temperature remains challenging. This study explores carbon dioxide detection using copper oxide thin films doped with sodium (CuO:Na), barium (CuO:Ba), erbium (CuO:Er), and vanadium (CuO:V), which were fabricated through spin-coating and annealed at 500 °C. All the films displayed a monoclinic tenorite structure, with crystallite sizes ranging from 23.8 to 59.5 nm, and band gaps that increased from 1.7 eV for pure copper oxide to 2.1 eV for copper oxide doped with vanadium (CuO:V). Among the various sensors, copper oxide doped with vanadium (CuO:V) exhibited the best performance, with a 248.3% response to 11100 ppm carbon dioxide at 30 °C and 45% relative humidity. It also had a response time of 7.4 s and a recovery time of 7.5 s. At 25% relative humidity, the response improved to 401.2%, reaching 1220% at 140 °C and 45% relative humidity. These findings highlight the potential of copper oxide doped with vanadium (CuO:V) for energy-efficient carbon dioxide detection, offering valuable contributions to environmental monitoring and efforts to mitigate climate change.